An AN ANALYSIS OF IDIOMS IN THE SPONGEBOB SQUAREPANTS CARTOONS - Muhammad Dwiky Rizaldy; Siti Aisyah (JournEEL, 2022)
Abstract This study was conducted to determine whether SpongeBob SquarePants Cartoons contains idioms, as there are some challenges in understanding and comprehending these idioms. A qualitative technique is used in this investigation. In this study, all utterances including or explaining idioms in SpongeBob SquarePants cartoons were used as primary data. The cartoon was evaluated by the researcher utilizing Seidl and McMordie's idioms theory (1988). According to the study's findings, there are two types of idioms, namely verb + preposition and verb + all types of words. The researcher found 6 data which are detailed as follows: for verb + preposition appeared 5 times and verb + all types of words was 1 times. Keywords: Idioms, Spongebob Squarepants Cartoons